Monte Carlo simulation of X-ray room shielding in diagnostic radiology using PHITS code - Suffian, Mohamad Tajudin; M.Z., Abdul Aziz; S., Yani (Taylor & Francis Group, 2020)
This research was conducted to evaluate scatter distribution at an X-ray room for diagnostic radiography using the Particle and Heavy Ion Transport code System (PHITS). The X-ray room was simulated using PHITS code based on the imaging room distance and length, as well as the control console room. The exact dimensions of the rooms were used as a geometry code in PHITS to simulate a point source isotopically with 100 keV energy in the X-ray room. There are three sources situated for this study which are source directed to the imaging table, inpatient bed, and Erect Bucky. Results show that PHITS simulation and measurement have a comparable value. The control console room is considered a safe place, based on the activation source from the simulation and measurement of the experimental dose with a dose ranged from 0.0540 to 0.1090 µSv per exposure. The control room is safe to the operator unless the number of cases handled is less than 11,086 cases per year. Comparison of dose distribution based on certain points of measurement and track detection from the simulation showed an approximate result. The dose obtained from the simulation and measurement is within the dose limits recommended by ICRP-60.